2002
DOI: 10.1074/jbc.m203572200
|View full text |Cite
|
Sign up to set email alerts
|

The Activation Function-1 Domain of Nur77/NR4A1 Mediates Trans-activation, Cell Specificity, and Coactivator Recruitment

Abstract: Nur77/NR4A1 is an "orphan member" of the nuclear hormone receptor superfamily. Nur77 and its close relatives Nurr1 and NOR-1 bind as monomers to a consensus binding site, the nerve growth factor induced protein I-B (NGFI-B)-binding response element (NBRE). The Nur77/ NURR1/NOR1 nuclear receptors are classified as immediate early response genes which are induced through multiple signal transduction pathways. They have been implicated in cell proliferation, differentiation, and apoptosis. However, the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 57 publications
(85 reference statements)
9
118
2
Order By: Relevance
“…Thus, a ligand-independent transcriptional activity of the NGFI-B/RXR complex that is readily formed after haloperidol-induced NGFI-B mRNA levels in the striatum (Beaudry et al, 2000) may be involved. Indeed, NGFI-B possesses an uncommonly potent activation function-1 (AF-1) domain that is essential for ligand-independent activation of gene expression, cofactor recruitment and interaction with RXR isoforms (Wansa et al, 2002). Thus, we can hypothesize that addition of a RXR agonist (9-cis RA or DHA) modifies the transcriptional activity of the complex (for a ligand-dependent activity) that interferes with haloperidol-induced effects.…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/mentioning
confidence: 99%
“…Thus, a ligand-independent transcriptional activity of the NGFI-B/RXR complex that is readily formed after haloperidol-induced NGFI-B mRNA levels in the striatum (Beaudry et al, 2000) may be involved. Indeed, NGFI-B possesses an uncommonly potent activation function-1 (AF-1) domain that is essential for ligand-independent activation of gene expression, cofactor recruitment and interaction with RXR isoforms (Wansa et al, 2002). Thus, we can hypothesize that addition of a RXR agonist (9-cis RA or DHA) modifies the transcriptional activity of the complex (for a ligand-dependent activity) that interferes with haloperidol-induced effects.…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/mentioning
confidence: 99%
“…[9][10][11] The endogenous signaling molecules that bind to Nurr1 are still unknown. 8 It has been previously shown that Nur77 and Nurr1 are expressed in bladder cancer cell lines. 12 However, the clinical significance in patients has not been reported.…”
mentioning
confidence: 99%
“…The nuclear orphan receptors are known to be immediate early response genes induced by a wide range of extracellular signals, including growth factors, apoptotic and inflammatory signals, and hormones, in a cell type-specific manner. 7,8 To our knowledge to date, Nurr1 has mainly been studied as a transcription factor in the nucleus. Mutations in the coding gene have been associated with neurologic diseases, including Parkinson disease, schizophrenia, and manic depression.…”
mentioning
confidence: 99%
“…We thus hypothesized that Pin1-induced TR3 transactivation may be associated with the recruitment of coactivators, such as p300, SRC1, SRC2 and SRC3, all of which were reported to enhance TR3 transactivation activity (Wansa et al, 2002;Maira et al, 2003). The results showed that p300 and the SRCs each promoted TR3 transactivation activity to a moderate degree.…”
Section: Pin1 Stabilizes Tr3 Protein By Blocking Its Degradationmentioning
confidence: 98%